An examination of how APRNs perceive sharing clinical notes with their patients - Laura Kay Wood; Deborah S. Adelman; Julia C. Koklys; Catherine Fant (The Nurse Practitioner, 2026)
ABSTRACT Background: As an outgrowth of a 2019 study and the pandemic, advanced practice registered nurse (APRN) attitudes toward sharing of clinical notes were explored. Methods: A quantitative, descriptive study approach was used to identify possible changes in APRN attitudes about sharing clinical notes with patients. A 20-question survey was administered through SurveyMonkey. Results: Among the 149 APRN participants, there was a split between those who felt it was a positive versus a negative experience. More than half expressed that sharing clinical notes influenced what they wrote and that it now took them longer to write their clinical notes. Conclusion: APRNs remain split about sharing clinical notes with patients. Concerns about patient understanding of content shared within clinical notes continue, and the value that results from sharing clinical notes remains unclear. The ultimate goal in sharing clinical notes is to improve patient care.